EFFECT OF EXTRACTION AND BLEACHING PROCESS ON THE CHEMICAL CHARACTERISTIC OF ALKALI TREATED COTTONII CHIPS (ATCC) - Puspita Puspita; Andi Sukainah; Ratnawaty Fadilah (JF Publisher, 2024)
Seaweed is one of the marine commodities with high economic value, because of its wide range of use, both in everyday life and in the industrial world, making the extraction process to test the physico-chemical properties of the quality of the extracted Euchema cottoni seaweed. This is an experimental research with a completely randomized design (CRD) factorial pattern consisting of 2 factors; the extraction process with 3 concentrations of KOH solution and the bleaching process with 3 concentrations of CaCO3 solution. This research aims to determine the effect of extraction and bleaching process on the physico-chemical characteristics of Alkali Treated Cottonii Chips (ATTC). The experiments were carried out by adding the concentration of KOH and CaCO3 solution in each treatment. The experiments showed that the concentration of KOH and CaCO3 solution in the processing process of Alkali Treated Cottonii Chips (ATTC) influenced the chemical physicochemical characteristics of Alkali Treated Cottonii Chips (ATTC). In this study, the lowest water content is treatment A3B1 obtained a value of 9.62% highest treatment AIB1 obtained a value of 11.77% where the maximum standard of ATTC water content is 12%, for the lowest pH is treatment A1B2 obtained a value of 9.06% highest treatment A3B2 obtained a value of 9.38% and the highest gel strength treatment A3B2 with a value of 193.10g lowest treatment A3B1 with a value of 66.50g while for the highest carrageenan treatment A1B2 with a value of 63.26% lowest treatment A3B3 with a value of 38.87%.